Rehabilitasi Fisioterapi untuk Akselerasi Pemulihan Pasien STEMI Anteroseptal CAD 1 VD Pasca Pemasangan DES Proksimal LAD TIMI Flow III di RSUD Dr.Moewardi Surakarta: Case Report - Muhammad Rais Hasan Firdaus; Farid Rahman; Ridwan Andi Susilo (JURNAL PENGABDIAN MASYARAKAT INDONESIA, 2026)
Coronary heart disease (CAD) remains a leading cause of death and disability worldwide. One of its most severe manifestations is ST-Elevation Myocardial Infarction (STEMI), particularly in the anteroseptal region, which is commonly caused by occlusion of the Left Anterior Descending (LAD) artery. Although reperfusion procedures such as Primary Percutaneous Coronary Intervention (PPCI) and Drug-Eluting Stent (DES) placement are effective in reducing mortality and restoring coronary blood flow, many patients still experience reduced functional capacity, impaired cardiac function, and decreased quality of life after treatment. These conditions highlight the importance of comprehensive and continuous rehabilitation following medical intervention. A structured physiotherapy approach based on the FITT (Frequency, Intensity, Time, Type) principle can be applied to support recovery and improve patient outcomes. This approach includes breathing exercises, walking training, and home-based exercise programs aimed at improving VO₂max, increasing functional capacity, enhancing cardiovascular endurance, and ultimately improving the overall quality of life in post-STEMI patients.